A Case of Amyopathic Dermatomyositis with Pneumomediastinum and Subcutaneous Emphysema - Aslıhan Gürün Kaya; Aydın Çiledağ; Orhan Küçükşahin; Özlem Özdemir Kumbasar; Çetin Atasoy (Case Reports in Rheumatology)
A 34-year-old man was admitted with dyspnea, cough, and fever. Thorax computed tomography revealed ground glass opacities and pneumomediastinum. The patient was diagnosed as amyopathic dermatomyositis due to skin lesions and radiological findings. Despite immunosuppressive treatment clinical deterioration and radiological progression were observed and the patient died because of severe hypoxemic respiratory failure. The patient presented with extremely rare occurrence of pneumomediastinum and subcutaneous emphysema in amyopathic dermatomyositis with a poor prognosis.